Effect of edible coatings on quality of mango fruit (Mangifera indica) 'Chok-Anan' during Storage - Phaiphan A. (2014)
Four coatings were used for treatment mango fruit, 'Chok-Anan'. These were 0.5% chitosan, 1% carboxymethyl-cellulose (CMC) with 2% propyleneglycol, butter emulsion (butter:water = 4:1) and non-coated control. During storage at 13±0.5°C, 93±2% relative humidity for 21 days, the fruit were analyzed to determine quality every 3 days. All three coatings reduced weight loss and respiration rate, delayed softening and peel and pulp color. Total soluble solids (TSS) content, reducing sugar, total sugar, and titratable acidity (TA) were slightly lower in coated fruits. The respiratory patterns of fruit coated with 0.5% chitosan and 1% CMC showed climacteric rise. Fermentation was induced in fruit coated with the butter emulsion. The pectin methylesterase activity increased at the beginning of storage and then decreased, while acid phosphatase activity decreased during the storage, but was not significantly different among treatments.